Pemetaan Konsumsi Energi Spesifik (Specific Energy Consumption) dan Neraca Massa Proses Pengolahan Teh Hijau di Pusat Penelitian Teh dan Kina (PPTK) Gambung - Akbar Fathurrachman; Reza Widyasaputra; Mukhammad Abdul Jabbar Filayati (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2026)
Green tea processing is an energy-intensive agro-industrial activity, particularly during the enzyme inactivation and multi-stage drying phases. Efficient use of energy in such facilities is essential for operational sustainability yet baseline data at the unit-process level remain scarce for Indonesian factories. This study aimed to (i) determine the mass balance and process yield, (ii) quantify the electrical and thermal Specific Energy Consumption (SEC) at each processing stage, and (iii) identify the primary energy-waste hotspots within the gate-to-gate boundary of the green tea production system at the Research Institute for Tea and Cinchona (PPTK) Gambung, West Java. Data were collected through direct field measurement (clamp meter, moisture analyser, and logsheets) across 8 production batches during January–March 2026. The total production yield was 19.82%, reflecting the large moisture reduction from fresh shoots (>75% moisture content, wet basis) to the final packaged dry product (<4%). Total SEC of the system reached 34.56 MJ/kg of product, dominated by the thermal energy load of 32.65 MJ/kg (94.48%), with electrical energy contributing 1.91 MJ/kg (equivalent to 0.5302 kWh/kg). Hotspot analysis identified the final drying unit (Ball tea) as the largest single consumer, accounting for the highest share of thermal energy load and exhibiting a low thermal efficiency of only 16.75%. The Rotary Panner (enzyme inactivation) and the Endless Chain Pressure (ECP, first-stage drying) also constituted significant thermal contributors. These findings indicate that improvement priorities should focus on thermal insulation and combustion system modernisation at the main heating units to reduce specific energy consumption and operational energy waste.